DUKUNGAN KELUARGA PADA ODHA YANG SUDAH OPEN STATUS DI KABUPATEN GARUT - Sukma Senjaya; Aat Sriati; Indra Maulana; Kurniawan Kurniawan (Jurnal Cakrawala Ilmiah, 2022)
This research is motivated by the large number of behavior of PLWHA families? People with HIV who experience anxiety are caused by negative stigma and discriminatory actions in social communities. This study aims to identify? the importance of family support for people with HIV who are open about their HIV status. This research uses quantitative descriptive with survey and observation. Data on HIV/AIDS from the Health Office in December 2018 said 253 people had HIV, 392 people had AIDS and 181 people died. The target achieved in this study was intended to determine the understanding and knowledge of the families of PLHAs and the support provided by families for PLWHA in their survival. With this achievement, it is expected that families can know the scope of HIV/AIDS so that families can overcome and prevent problems regarding HIV/AIDS. Based on the results of research on Family Support for PLWHA at the TNI AD Guntur Garut Hospital, the results showed that most of the respondents gave support with a presentation of 80%. And the lowest percentage of support is 20%. This is in line with research (P. S. Chandra, Deepthivarma, & Manjula, 2017) about 45% of subjects felt that disclosure could cause labeling by others or attribute their illness as a pointer to their character. HIV disclosure can lead to important social support that can reduce negative effects. The conclusion is based on the results of a study entitled Family Support for PLWHA Who Have Open Status at the Hospital. TNI AD Guntur Garut Regency was conducted on 10 respondents, the results showed that family support for PLWHA mostly supported 80% of HIV in the TNI ADGuntur Garut Hospital which had the highest perception of aspects